Evolving Gender-Sensitive Transitional Justice: A Way to Ensure Healing and Equality in Sudan - Slom, Fawzi Ahmed Abdullah (New Ideas Concerning Arts and Social Studies Vol. 1, 2025)
The conflict in Sudan has significantly eroded the advancements made toward democracy and stability, resulting in unprecedented suffering and insecurity for the country and precipitating a catastrophic humanitarian crisis. In the aftermath of conflict, societies grapple with the need for justice, healing, and reconciliation. In Sudan, a country scarred by decades of violence and upheaval. This study explores the critical need for gender-sensitive transitional justice in Sudan, highlighting its potential to address historical injustices and promote healing among affected populations. It examines the concept of transitional justice, emphasizing the importance of incorporating gender perspectives into truth-seeking, reparations, and institutional reforms. The analysis is grounded in the historical context of gender inequality in Sudan and the impact of conflict on women and marginalized groups. Case studies of successful gender-sensitive initiatives illustrate their effectiveness and potential for replication. The study draws on qualitative data collected through interviews with key stakeholders, including survivors, civil society organizations, and advocacy groups, as well as a review of relevant literature and policy documents. Findings suggest that inclusive engagement and the active participation of diverse voices are essential for shaping effective transitional justice mechanisms that foster equality and sustainable peace. The study concluded that advancing gender-sensitive transitional justice in Sudan is essential for fostering healing, equality, and peace. Incorporating gender perspectives into truth-seeking, reparations, and institutional reforms will address the specific needs of women and marginalised groups, ensuring their voices are recognised and valued.